2013
DOI: 10.1158/1940-6207.capr-12-0458
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Social Isolation Is Associated with Metabolic Gene Expression Changes Specific to Mammary Adipose Tissue

Abstract: Chronic social isolation is linked to increased mammary tumor growth in rodent models of breast cancer. In the C3(1)/SV40 T-antigen FVB/N (TAg) mouse model of “triple-negative” breast cancer, the heightened stress response elicited by social isolation has been associated with increased expression of metabolic genes in the mammary gland before invasive tumors develop (i.e. during the in situ carcinoma stage). To further understand the mechanisms underlying how accelerated mammary tumor growth is associated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 55 publications
1
34
1
Order By: Relevance
“…Males with B6.FVB background display aggressive behavior and they could not be housed together. Social isolation generates undesirable physiological and brain effects that can be permanent (Volden et al 2013 ). Each male to be tested was housed with a female to avoid these biases.…”
Section: Housingmentioning
confidence: 99%
“…Males with B6.FVB background display aggressive behavior and they could not be housed together. Social isolation generates undesirable physiological and brain effects that can be permanent (Volden et al 2013 ). Each male to be tested was housed with a female to avoid these biases.…”
Section: Housingmentioning
confidence: 99%
“…We previously reported that the chronic stressor of early social isolation is associated with increased metabolic gene expression of several genes encoding important glucose flux and lipid metabolism proteins (hexokinase 2, ATP citrate lyase, and acetyl-CoA carboxylase alpha) within the mammary adipocytes of 15 week old female mice (12). Increased expression of these particular enzymes was predicted to increase glucose flux into lipid synthesis, which was confirmed (12).…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that exposure to this form of chronic social stress is also associated with upregulation of genes mediating conversion of glucose to lipids in mammary adipocytes of female SV40 TAg mice, and a concomitant increase in de novo lipid synthesis (12). Furthermore, serum-free medium pre-incubated with mammary fat (conditioned medium) caused significantly augmented proliferation of Tag mouse mammary epithelial cells (MECs) (12). These data suggested that alterations in mammary adipocyte metabolism and associated changes in the mammary fat secretome could alter the local microenvironment and contribute to TNBC progression.…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic innervation was detected during premalignancy, coursing amongst adipocytes. This finding raises the possibility that SNS hardwiring of mammary adipose tissue is a mechanism by which catecholamines can regulate adipocytes and, mammary adipose tissue metabolism to modulate early mammary tumor progression (Volden et al, 2013; Zhang et al, 2009). The sparse TH+ sympathetic innervation detected in late-stage adenocarcinoma reflects the restricted distribution of sympathetic innervation to blood vessels and smooth muscle in the normal mammary gland (Eriksson et al Neuroscience, 1996).…”
Section: Discussionmentioning
confidence: 98%